2002
DOI: 10.1038/sj.onc.1205513
|View full text |Cite
|
Sign up to set email alerts
|

A p53-p66Shc signalling pathway controls intracellular redox status, levels of oxidation-damaged DNA and oxidative stress-induced apoptosis

Abstract: Correlative evidence links stress, accumulation of oxidative cellular damage and ageing in lower organisms and in mammals. We investigated their mechanistic connections in p66Shc knockout mice, which are characterized by increased resistance to oxidative stress and extended life span. We report that p66Shc acts as a downstream target of the tumour suppressor p53 and is indispensable for the ability of stress-activated p53 to induce elevation of intracellular oxidants, cytochrome c release and apoptosis. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
359
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(388 citation statements)
references
References 26 publications
23
359
3
3
Order By: Relevance
“…Indeed, this mouse strain is characterised by a 30% extension of lifespan, 8 a decrease in the levels of in vivo systemic and tissue oxidative stress and vascular apoptosis, 9 and by an abrogation of oxidative stress-induced, p53-dependent apoptosis. [8][9][10] Together with other literature data, these results suggest that p53-dependent mechanisms are candidates to play a crucial role in the pathogenesis of agerelated diseases, such as atherosclerosis and myocardial dysfunction, that is, the major causes of morbidity and mortality among elderly people. [11][12][13][14] In humans, the age of the donor affects the in vitro susceptibility to oxidative stress-induced apoptosis, but a wide interstudy and interindividual variability has been reported.…”
Section: Introductionsupporting
confidence: 70%
“…Indeed, this mouse strain is characterised by a 30% extension of lifespan, 8 a decrease in the levels of in vivo systemic and tissue oxidative stress and vascular apoptosis, 9 and by an abrogation of oxidative stress-induced, p53-dependent apoptosis. [8][9][10] Together with other literature data, these results suggest that p53-dependent mechanisms are candidates to play a crucial role in the pathogenesis of agerelated diseases, such as atherosclerosis and myocardial dysfunction, that is, the major causes of morbidity and mortality among elderly people. [11][12][13][14] In humans, the age of the donor affects the in vitro susceptibility to oxidative stress-induced apoptosis, but a wide interstudy and interindividual variability has been reported.…”
Section: Introductionsupporting
confidence: 70%
“…Oxidative stress shortens telomeres (von Zglinicki, 2002), and the deletion of p66SHC reduces oxidative stress (Trinei et al ., 2002 and Fig. 3A and B).…”
Section: Discussionmentioning
confidence: 86%
“…Eight‐hydroxy‐2‐deoxy guanosine (8‐OH‐dG) and isoprostanes are recurrent oxidized DNA base and fatty acids products, respectively, that marks oxidative stress to DNA and lipids and were found reduced in p66SHC −/− mice (Trinei et al ., 2002; Napoli et al ., 2003; Lunghi et al ., 2015). We have measured the content of 8‐OH‐dG in the genomic DNA extracted from liver, spleen, lung, and testis of G0 and G3; and liver and spleen of G5 TERC −/− p66SHC +/+ or TERC −/− p66SHC −/− 6‐month‐old mice using a competitive ELISA assay with specific anti‐8‐OH‐dG antibody and of 8‐iso‐PGF2α (8‐isoprostane) by immunohistochemistry analysis of tissue sections from testis, lung, and liver of G0 and G3, TERC −/− p66SHC +/+ , and TERC −/− p66SHC −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone cells, one important effect of FoxO activation is that this transcription factor binds β-catenin to promote the expression of antioxidant gene program but avoiding that β-catenin might drive the transcription of several genes implicated in osteoblastic function (Almeida et al 2007a;Hoogeboom et al 2008). Other consequences of ROS increase include lipid peroxidation and phosphorylation of p66 Shc leading to an increase in osteoblast and osteocyte apoptosis (Trinei et al 2002;Almeida et al 2007a).…”
Section: Introductionmentioning
confidence: 99%